Imunidades tributárias: considerações sobre sua aplicação formalista - Bettencourt, Artur Henrique Rios Tavares Machado (2020)
The purpose of this paper is to analyze the tax immunities provided in the article 150, VI, of the Brazilian Federal Constitution, in order to find a path to its interpretation and application in a safe manner and in accordance with the constitutional tax system. To reach this goal, we will initially proceed to a comparison between immunities and the rules of tax jurisdiction, pointing out their main characteristics, similarities and differences. Then, we will analyze the philosophical foundation of immunities and the historical evolution of the State's action, looking for a comprehensive understanding of the tax system based on the protection of human rights, on one hand, and on the need State’s need to obtain resources in order to promote its goals. Finally, we will study the theme of interpretation of Law, in general, and Tax Law, specifically, addressing some theories that predominated in certain periods, the main methods of interpretation, as well as the opposition between the neo-constitutionalist theory, which defends the application of constitutional norms with the prevalence of principles over rules, establishing the role of the judges, and normative formalism, which highlights the importance of rules as sufficient reasons to justify decisions, regardless of other factors that could be considered relevant. Based on the demonstration that tax immunities are rules and the importance of these norms for the normative certainty of the constitutional tax system, we will try to demonstrate that tax immunities, regardless of whether they are related to fundamental principles and rights, must be interpreted and applied in a formalista way, within the limits of the constitutional text